PERANAN PERBANKAN BAGI PENGEMBANGAN USAHA PETANI JERUK DI KAB. KARO - Wina Safebrina Pinem; Sya'ad Afiffuddin (Departemen Ekonomi Pembangunan USU, 2014)
The problems of this research is how the influence of their own capital, loan capital and land held against citrus growers citrus farmers in business development Karo can be seen from the increase in revenue. The purpose of this research is to analyze their own capital, loan capital and land that may affect the business improvement particularly in citrus growers Karo seen from the increase in revenue. The hypothesis of this study is that there is a positive effect of own capital, credit capital and land area of the business improvement citrus growers who have seen improved citrus farmers' income in Karo District. Data analysis methods used are simple linear regression analyzes were used to see how the influence of their own capital, loan capital and land that may affect the business improvement / citrus farmers' income, as well as the correlation coefficient is used to see the closeness of the relationship between the variables of their own capital, capital credit and land on citrus farmers' income. The results showed that the positive influence of capital, loan capital and land area of the business improvement / citrus farmers' income significantly, and there is a correlation between the equity, capital and credit to an increase in the land area of business / revenue and positively perfect.Keywords:Equity, Capital Credit, Land Area and Revenue